2016
DOI: 10.1016/j.engfracmech.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of KI calculation methods

Abstract: This paper compares different numerical methods for mode I stress intensity factor (SIF) calculations. Both 2D and 3D models are used to calculate KI for the compact tension specimens. J-integral and interaction integral provide relatively accurate results. The analysis of a reactor pressure vessel subjected to pressurized thermal shock is performed using the finite element method (FEM) and extended finite element method (XFEM). XFEM method shows advantages in modeling cracks but oscillations in 3D problems du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…These methods are based on displacement extrapolation and/or energetic approach such as integral J/integral interaction. Methods detailed in the reference Qian [12]. Zhu [13] showed that the energy approach provides good result in com- parison with analytical results, reason why the computation of factor KI by the energetic approach is independent of the mesh near the crack.…”
Section: Stress Intensity Factor Kimentioning
confidence: 88%
“…These methods are based on displacement extrapolation and/or energetic approach such as integral J/integral interaction. Methods detailed in the reference Qian [12]. Zhu [13] showed that the energy approach provides good result in com- parison with analytical results, reason why the computation of factor KI by the energetic approach is independent of the mesh near the crack.…”
Section: Stress Intensity Factor Kimentioning
confidence: 88%
“…In this study, the interaction integral is employed to extract the SIF; this method has been implemented in commercial ABAQUS. Qian et al 35 have compared different numerical methods for calculating SIF. They have concluded that the SIF calculated by interaction integral is an appropriate method to determine accurate SIF values for 3 D cracks.…”
Section: Repaired Platementioning
confidence: 99%
“…Meanwhile, the hexahedron elements are added outside to improve the calculation accuracy. 18,19 The finite element model of crossbores with a crack at the intersecting line is shown in Figure 4. Specifically, the structure of crossbores is shown in Figure 4(a), and the crossbore model with meshes is shown in Figure 4(b).…”
Section: Boundary Conditionsmentioning
confidence: 99%